2017
DOI: 10.1590/2317-1545v39n3160444
|View full text |Cite
|
Sign up to set email alerts
|

Seedling image analysis and traditional tests to evaluate onion seed vigor

Abstract: -The aim of this study was to verify the possibility of using computerized seedling image analysis to detect differences in vigor among onion seed lots and to compare this analysis with traditional vigor tests. We used five seed lots of two onion cultivars, Bella Catarina and Bella Vista. The Seed Vigor Imaging System (SVIS ® ) software was used to process the seedling images and assess seedling length and vigor through seedling uniformity and growth indexes. These determinations were compared to traditional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
(20 reference statements)
0
7
0
3
Order By: Relevance
“…According to Hinkle et al (2003), a strong linear relationship between two variables show values higher than 0.8; however, in physiological tests of rice (Lorentz and Nunes 2013) and onion seeds (Gonçalves et al 2017) suggested as acceptable values above 0.6 and 0.7, respectively. Nevertheless, due to the natural vigor and germination differences that may exist across seed lots within the same crop, there are no fixed reference values for interpreting the Pearson coefficient in the area of seed testing, demanding that a dataset analysis specific reading for a given sample set.…”
Section: Resultsmentioning
confidence: 98%
“…According to Hinkle et al (2003), a strong linear relationship between two variables show values higher than 0.8; however, in physiological tests of rice (Lorentz and Nunes 2013) and onion seeds (Gonçalves et al 2017) suggested as acceptable values above 0.6 and 0.7, respectively. Nevertheless, due to the natural vigor and germination differences that may exist across seed lots within the same crop, there are no fixed reference values for interpreting the Pearson coefficient in the area of seed testing, demanding that a dataset analysis specific reading for a given sample set.…”
Section: Resultsmentioning
confidence: 98%
“…Recent studies with the use of seedling image analysis have indicated evaluations at two days after sowing for maize (Mondo et al, 2011) and millet (Javorski et al, 2018) seeds; three to four days for common bean (Gomes-Junior et al, 2014), soybean (Marcos-Filho et al, 2009;Medeiros and Pereira, 2018), crambe (Leão-Araújo et al, 2017), and sunflower (Rocha et al, 2015) seeds; and five to six days for onion (Gonçalves et al, 2017) and carrot (Marchi and Cicero, 2017) seeds.…”
Section: Resultsmentioning
confidence: 99%
“…According to Gonçalves et al (2017), the correlation between the traditional tests and image analysis is valuable for adjusting the method, especially for determining the best age of the seedlings to carry out analysis. In this sense, the strong correlation with widely used vigor tests shows the Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, research in seed technology has prioritized high-throughput seedling phenotyping to evaluate seed vigor in order to minimize these limitations in the analyses. Robust semi-automated phenotyping systems capable of generating reliable data have been shown to be efficient for evaluating squash (Silva et al, 2017), onion (Gonçalves et al, 2017), carrot (Marchi & Cicero, 2017), crambe (Leão-Araújo et al, 2017), corn (Castan et al, 2018;, soybean seedlings Wendt et al, 2017;Yagushi et al, 2014), among others. Among the options available for this purpose is the Seedling Analysis System (SAPL ® ).…”
Section: Introductionmentioning
confidence: 99%